PENGARUH KEPUASAN GAJI, KEPUASAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP INTENSI KELUAR: PENGUJIAN EMPIRIS MODEL TURNOVER LUM et. al. - HARIF AMALI RIVAI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2001)
This study examines both direct and indirect effect pay satisfaction, job satisfaction, and organizational commitment upon the turnover intentions. A number of models have been develop to explain turnover behavior. The common theme that emerges from these models is that turnover behavior is a multistage process taht includes attitudinal, decisional, and behavioral component. The purpose of this study was to assess what model accurate portrays the relationship among pay satisfaction, job satisfaction, and organizational commitment upon the turnover intentions. The respondents were nurses. The sampling method used convenience sampling. There are 180 questionnaires was distributed, 168 was returned, nevertheless 132 questionnaires (73%) was entered analysis. Data analysis research that used is structural equation modeling with AMOS program aplicantions. The hypothesized relationship was formulated as a causal model. The result of the study supported that job satisfaction has an indirect influence on the intentions to quit, and organizational commitment has direct effect on turnover intent. This finding also supported that pay satisfaction had both direct and indirect effect on turnover intent. Job satisfaction was a significant antecedent to organizational commitment and variable that highes correlation on turnover intent.